A combined method for the treatment of grade IV internal haemorrhoidal disease - Georgios-Ioannis Verras; Francesk Mulita; George Theofanis; Levan Tchabashvili; Ioannis Perdikaris; Theano Perri; Charalampos Kaplanis; Dimitrios Filis (Gastroenterology Review)
A 48-year-old patient presented acutely in our emergency department, reporting a fainting episode that took place several minutes prior, as well as continuous rectal blood loss. The patient’s prior medical history included known grade IV haemorrhoidal disease for the past 33 years, as well as one more instance of hospitalization for haemorrhoid-associated blood loss. Examination of the patient’s vital signs revealed a blood pressure of 98/67 mm Hg and a pulse rate of 68 bpm, while the respiratory rate and temperature were within the normal limits. Anorectal inspection revealed massive, grade IV internal haemorrhoidal disease, with numerous prolapsed and ulcerated haemorrhoids as well as active bleeding sites. Digital palpation of the rectum returned stool of normal consistency, as well as ample fresh blood. Complete blood count report returned hemoglobin (Hb) values of 7.0 g/dl and hematocrit (Hct) of 24.3% in addition to marked neutrophilia (73.9%), indicating severe acute blood loss.